(untitled) - Gookin, Dan (New Jersey, 2005)
Targeting the snags, glitches, and predicaments cited most frequently by readers, bestselling author Dan Gookin clearly explains how to diagnose and cure common PC problems, whether they originate with software, the operating system, or hardware. This updated edition features new, expanded coverage of laptop woes as well as Internet and e-mail issues, broadband connections, spam blocking, and security concerns. Provides advice on how to prevent PC problems in the first place and create a safe and secure PC environment, and Dan Gookin is known for his ability to explain technology in an easy-to-understand and enjoyable fashion; his writing style, name, and reputation are unparalleled in the industry.
Keywords: Microsoft windows (computer file),Operating systems (Computers)